Identifikasi Hubungan Antara Kepemimpinan dan Kepuasan Kerja - Wahyuningsih -; Roni Zakaria; Rahmaniyah D A (Performa: Media Ilmiah Teknik Industri, 2004)
The Fully Articulated Transactional Model of Leadership identificated that leadership is built by the transaction of three power, there’re leader, follower and situation. The interaction between three power above influenced follower motivation which can decided job satisfaction level. The aim of this research is to decide the relationship’s design between job satisfaction and leadership factor that significantly influenced employee job satisfaction.The research is done in production departement of Panjang Factory when happened productionsystem connection development training. When training occurs, reasearcher found there’re employees that not finished case study given by leader and writtent the stetement which more relative to unobjective leadership of the leader phenomenas. The condition suggested employees weren’t satisfied which the leader which undirectly explained.The respondent used in this research consisted 65 peoples in production department of PanjangFactory, there’re 60 direct employee, leader, quality control and machine keeping, supervisor, and production manager. The research showed that the increasing of job satisfaction is significantly influenced by six leadership factors those’re increasing of idealized influence, participative goal setting, condition of task executing, personal identification, respect of task’s knowledge and ability factors and also the declining of social identification factor.